Penerapan Manajemen Resiko Persediaan Terhadap Efisiensi Oprasional Pada Kafe Rosella - Muliani Syapitri; Sarah Shabrina; Karina Azzahra; Siti Maharani Nst; Arsyadona A (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the application of inventory risk management in Rosella Cafe as an effort to improve operational efficiency and financial stability. By using the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods, this study found that this strategy can save inventory costs of up to Rp 119,992.74 per year compared to the manual method that has been applied by the rosella café flat. The results show that the implementation of EOQ and ROP not only helps in determining the optimal number and time of order, but can also ensure the timely availability of raw materials, reduce the risk of shortage or excess stock, and support smooth operations. This research is expected to be an example for other small businesses in managing inventory effectively in the increasingly competitive food and beverage industry